2002
DOI: 10.1016/s0140-6736(02)07811-x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid injections, physiotherapy, or a wait-and-see policy for lateral epicondylitis: a randomised controlled trial

Abstract: Patients should be properly informed about the advantages and disadvantages of the treatment options for lateral epicondylitis. The decision to treat with physiotherapy or to adopt a wait-and-see policy might depend on available resources, since the relative gain of physiotherapy is small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
472
1
47

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 665 publications
(546 citation statements)
references
References 19 publications
26
472
1
47
Order By: Relevance
“…Os efeitos a longo prazo do uso de corticosteróides são menos favoráveis que a curto prazo (58) . Porém, quando o corticosteróide é aplicado na região peritendínea, pode trazer efeitos bené-ficos (59) .…”
Section: Tratamento Conservadorunclassified
“…Os efeitos a longo prazo do uso de corticosteróides são menos favoráveis que a curto prazo (58) . Porém, quando o corticosteróide é aplicado na região peritendínea, pode trazer efeitos bené-ficos (59) .…”
Section: Tratamento Conservadorunclassified
“…A wide variety of non-surgical treatments are available, including ultrasound, non-steroidal anti-inflammatory drugs, corticosteroid injections, a forearm brace or orthotics, stretching, eccentric exercise, and taping 2,[20][21][22][23][24] . Oral and topical non-steroidal antiinflammatory drugs and corticosteroid injection may be helpful for breaking the pain cycle 25) .Smidt compared the efficacy of physiotherapy and corticosteroid injections and found that corticosteroid injection was superior to all other therapies; however, corticosteroid treatment was associated with a high recurrence rate 26) .…”
Section: Introductionmentioning
confidence: 99%
“…A diferença estimada na alteração desta escala (IC 95%) comparativamente à avaliação inicial pré-intervenção foi de -2,4 (-8,1 a 3,4) às quatro semanas de seguimento e -2,9 (-9,0 a 3,2) às 12 semanas. 20 Em relação à perspectiva do doente, dos três estudos que analisaram a satisfação global do doente, 14,15,17 um apresenta uma média de satisfação de 3,97 (DP 2,26) numa escala numérica em que zero corresponde a 'não satisfeito' e seis a 'muito satisfeito'; 14 noutro estudo o índice de satisfação às seis semanas foi de 90% (DP 16%) e às 52 semanas de 77% (DP 23%) num universo de 62 doentes avaliados.…”
Section: Resultsunclassified
“…15 Os efeitos adversos ligeiros atribuídos às infiltrações de corticosteróides, a nível sistémico, incluíram afrontamentos, [13][14][15][16][17]19 alterações do ciclo menstrual, 13,16,17 Os três estudos de custo-efectividade analisaram os encargos financeiros e o efeito das infiltrações peri-articulares de corticósteroides na qualidade de vida dos indivíduos com síndrome do ombro doloroso, sendo que nenhum dos estudos fez referência a efeitos adversos. [21][22][23] O estudo de James et al mostrou encargos financeiros totais, por doente, de 100,50€ para o grupo sujeito a infiltrações e 161,59 € para o grupo submetido a fisioterapia, sendo a diferença média, por doente, de 61,08 € (IC 95%, 22,86 € a 95,92 €).…”
Section: Resultsunclassified